2018
DOI: 10.1177/0269881118806297
|View full text |Cite
|
Sign up to set email alerts
|

3,4-Methylenedioxymethamphetamine-assisted psychotherapy for treatment of chronic posttraumatic stress disorder: A randomized phase 2 controlled trial

Abstract: Background:Posttraumatic stress disorder often does not resolve after conventional psychotherapies or pharmacotherapies. Pilot studies have reported that 3,4-methylenedioxymethamphetamine (MDMA) combined with psychotherapy reduces posttraumatic stress disorder symptoms.Aims:This pilot dose response trial assessed efficacy and safety of MDMA-assisted psychotherapy across multiple therapy teams.Methods:Twenty-eight people with chronic posttraumatic stress disorder were randomized in a double-blind dose response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
203
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 175 publications
(212 citation statements)
references
References 56 publications
7
203
1
1
Order By: Relevance
“…This hypothesis is in good agreement with the positive effects obtained by injecting the anxiolytic drug propranolol in cocaine addicted 72 or PTSD 73 patients before their respective exposure to drug-craving stimuli or to PTSD cues. It is also consistent with the evaluation of the recent advancements in MDMA-assisted psychotherapy for PTSD 74,75 which points out that treatments that block pathological activation in brain regions implicated in the expression of fear during the memory malleability phase are likely to induce re-processing of traumatic memories. This new memory with a lower emotional component could therefore reduce the forthcoming impact of the trauma.…”
Section: Emotional Remodeling With Oxytocin: What Mechanisms?supporting
confidence: 85%
“…This hypothesis is in good agreement with the positive effects obtained by injecting the anxiolytic drug propranolol in cocaine addicted 72 or PTSD 73 patients before their respective exposure to drug-craving stimuli or to PTSD cues. It is also consistent with the evaluation of the recent advancements in MDMA-assisted psychotherapy for PTSD 74,75 which points out that treatments that block pathological activation in brain regions implicated in the expression of fear during the memory malleability phase are likely to induce re-processing of traumatic memories. This new memory with a lower emotional component could therefore reduce the forthcoming impact of the trauma.…”
Section: Emotional Remodeling With Oxytocin: What Mechanisms?supporting
confidence: 85%
“…Results from these trials demonstrate that MDMA-assisted psychotherapy produces significant reductions in PTSD symptoms (Mithoefer et al, 2018; DOI: 10.1002/jts.22479 This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. 2011; Oehen, Traber, Widmer, & Schnyder, 2013;Ot'alora et al, 2018) and that these reductions endure (Mithoefer et al, 2013). Results of a pooled analysis of six Phase 2 studies (Mithoefer et al, 2019) demonstrated that two psychotherapy sessions with active doses of MDMA more than doubled PTSD symptom reduction compared to psychotherapy with placebo controls (estimated mean difference between groups = −22.0, SE = 5.17), d = 0.8.…”
mentioning
confidence: 99%
“…Studies that have considered the efficacy of psychotherapeutic interventions following unsuccessful evidencebased PTSD treatment for veterans and other TR-PTSD populations are very scarce [51]. Results of multiple trials with 3,4-methylenedioxymethamphetamine (MDMA)assisted psychotherapy for TR-PTSD were encouraging with large effect sizes [52][53][54][55], and deep brain stimulation shows promise as well, with two positive case reports [56]. Considering that the current trial recruited veterans with, on average, 4 prior unsuccessful treatments and demonstrated a large effect size, 3MDR could prove to be a useful non-invasive, non-pharmacological addition to the toolbox of clinicians working with veterans with TR-PTSD.…”
Section: Interpretation and Comparison To Existing Studiesmentioning
confidence: 99%